Assessment of Small Ruminant Welfare in Ethiopia – An Abattoir-Based Study. Issue 3 (2nd July 2020) - Bekele, Tizeta; Szonyi, Barbara; Feleke, Aklilu; Grace, Delia
ABSTRACT: This paper presents the results of a cross-sectional study assessing the welfare of sheep and goats in a large abattoir in central Ethiopia, using qualitative and quantitative approaches. A total of 384 nonhuman animals (192 sheep and 192 goats) underwent clinical examination and behavioral observation in 2014. The study also included behavioral observation of 57 animal handlers, and a qualitative assessment of animal welfare conditions at the abattoir. Clinical examination revealed dirty wool/hair (54.9%), poor body condition (15.8%), and respiratory disorders (14.0%). The most commonly observed behaviors were refusing to move (17.1%), panting (15.8%) and reversing (10.4%). Significantly higher proportion of sheep exhibited resistance behaviors such as refusing to move (21.4% of sheep and 13.0% of goats; p < 0.030) and resistance to being pulled (12.5% of sheep and 6.3% of goats; p < 0.0036). Handlers frequently beat (87.7%), pushed (57.9%) and pulled (49.1%) the animals. Poor handling of animals was very common and could result in animal distress and falls. In collaboration with the abattoir workers, the authors developed simple good practice to improve welfare and reduce losses from poor welfare.